Microwave-Assisted Synthesis of Selenium Nanoparticles: Bioactivity Insights - Tisli, Buesra; Nejati, Omid; Torkay, Gulsah; Giray, Betul; Bal-Ozturk, Ayca; Bakirdere, Sezgin (WILEY-V C H VERLAG GMBH, 2024)
Selenium is a well-known element that can be toxic and potentially harmful in excessive amounts. In this study, the microwave-assisted synthesis of selenium nanoparticles (SeNP) was achieved using glucose as a green reductant, resulting in reduced toxicity. This method provides a rapid, cost-effective, and environmentally friendly alternative to traditional SeNP synthesis techniques. The antioxidant activity of the SeNPs was assessed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, while their antibacterial properties were tested against both Gram-positive (E. coli) and Gram-negative (S. aureus) bacteria using the agar diffusion method. Additionally, the cytotoxicity of SeNPs towards the Beas2B cell line was evaluated using the MTT viability assay at various concentrations. Results produced confirm the successful synthesis of SeNPs with notable antioxidant and antibacterial properties through a simple and economical approach, indicating potential applications in various fields.
Keywords: Antibacterial; Antioxidant; Cytotoxicity; Microwave assisted method; Selenium nanoparticles; GREEN SYNTHESIS; NEW-GENERATION; SILVER; NANOSTRUCTURES; BIOSYNTHESIS; Chemistry